2019
DOI: 10.14309/ajg.0000000000000136
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Dynamics in the Gut Microbiota Precede Crohn's Disease Flares

Abstract: OBJECTIVES: Crohn's disease (CD) is a chronic relapsing-remitting gut inflammatory disorder with a heterogeneous unpredictable course. Dysbiosis occurs in CD; however, whether microbial dynamics in quiescent CD are instrumental in increasing the risk of a subsequent flare remains undefined. METHODS: We analyzed the long-term dynamics of microbial composition in a prospective observational cohort of patients with quiescent CD (45 cases, 217 samples) over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 37 publications
1
56
0
1
Order By: Relevance
“…TNF and Interferon-γ) regulate intestinal epithelial proliferation at the crypt base 29,30 , inducing or restricting intestinal epithelial proliferation and cell death 31,32 depending on the circumstances. Differences between Crohn disease and celiac disease in this respect may be driven by the role of the gut microbiota that was already linked to Crohn disease pathogenic processes in several large cohorts 33 . The role of microbiota in celiac disease was linked to different metabolic patterns of gluten break down 34 and was shown to be different in infants with an affected first degree relative 35 , but the overall microbial composition has not yet been fully defined in large human cohorts of celiac disease, and is still controversial 36 .…”
Section: Discussionmentioning
confidence: 99%
“…TNF and Interferon-γ) regulate intestinal epithelial proliferation at the crypt base 29,30 , inducing or restricting intestinal epithelial proliferation and cell death 31,32 depending on the circumstances. Differences between Crohn disease and celiac disease in this respect may be driven by the role of the gut microbiota that was already linked to Crohn disease pathogenic processes in several large cohorts 33 . The role of microbiota in celiac disease was linked to different metabolic patterns of gluten break down 34 and was shown to be different in infants with an affected first degree relative 35 , but the overall microbial composition has not yet been fully defined in large human cohorts of celiac disease, and is still controversial 36 .…”
Section: Discussionmentioning
confidence: 99%
“…74,91,102,123,152,180,181 Even the associations we have identified might be used as biomarkers and to develop functional assays for more timely disease detection and more accurate risk calculation. 91,182…”
Section: Future Directionsmentioning
confidence: 99%
“…These studies demonstrated that age, gender, and ethnicity are associated with the abundance of Christensenellaceae . The relative abundance of Christensenellaceae in the intestine was found to be inversely proportional to body mass index (BMI) ( Fu et al, 2015 ; Goodrich et al, 2014 ; Oki et al, 2016 ; Peters et al, 2018b ) and exhibited a negative correlation with obesity and inflammatory bowel disease ( Braun et al, 2019 ; Gevers et al, 2014 ; Imhann et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%